Comparative biochemical and structural characterizations of fungal polygalacturonases - Niture, Suryakant K. (Biologia, 2008)
Endo- and exo-polygalacturonases produced by various fungi are involved in the degradation of pectic substances. They have found a wide range of applications in the food and textile industries. Several phyto-pathogenic fungi secrete polygalacturonases and they act as virulence factors during plant pathogenesis. The comparison of biochemical properties of different fungal polygalacturonases, their mechanism of actions, structural aspects and interactions with inhibitors/proteins could be used as a possible strategy for the fungal-crop disease management. This review focuses on fungal polygalacturonases, including their regulation, comparative biochemical and structural characterizations and their interactions with inhibitors.
Keywords: pectate lyase; plant pathogenesis; polygalacturonase; polygalacturonase-inhibiting proteins